1993
DOI: 10.1002/gcc.2870060405
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 12‐containing markers, including two dicentrics, in three i(12p)‐negative testicular germ cell tumors

Abstract: A chromosome 12-derived marker was seen in each of 3 testicular germ cell tumors that lacked the i(12p). An interesting feature of 2 of the markers was that the major part, including the centromere, of an acrocentric (a #13 and #14, respectively) was translocated onto 12p, resulting in a dicentric. In the third tumor, 13q (translocated onto 12q) was again probably involved in the rearrangement. The findings support the view that the amplification of genes on 12p represents a significant step in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The most consistent CGH finding was additional 12p material, which is in keeping with the i(l2p) chromosome found in 80% of TGCT and the over-representation of 12p material determined in FISH studies of i(12p) negative cases (Atkin et al, 1993;Rodriguez et al, 1993;Suijkerbuijk et al, 1993). Cases with additional copies of the 12pl 1.2-12.1 region have been previously reported, suggesting that a subgroup of TGCT amplifies this region (Suijkerbuijk et al, 1994;Korn et al, 1996;Mostert et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most consistent CGH finding was additional 12p material, which is in keeping with the i(l2p) chromosome found in 80% of TGCT and the over-representation of 12p material determined in FISH studies of i(12p) negative cases (Atkin et al, 1993;Rodriguez et al, 1993;Suijkerbuijk et al, 1993). Cases with additional copies of the 12pl 1.2-12.1 region have been previously reported, suggesting that a subgroup of TGCT amplifies this region (Suijkerbuijk et al, 1994;Korn et al, 1996;Mostert et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…Approximately 80% of TGCT are associated with an isochromosome 12p (Atkin and Baker, 1983;Rodriguez et al, 1992;van Echten et al, 1995) and in i(12p) negative cases over-representation of the short arm of chromosome 12 has been demonstrated (Atkin et al, 1993;Suijkerbuijk et al, 1993;Rodriguez et al, 1993). Cytogenetic studies have not identified any other highly consistent chromosome rearrangements that are associated with this group of tumours, although gains and losses of particular chromosomes have been noted (Rodriguez et al, 1992;Mitelman, 1994;van Echten et al, 1995).…”
mentioning
confidence: 99%
“…T h e most common finding has been an i(12p), seen in approximately 80% of all histologic subsets (Atkin and Baker, 1982, 1983Delozier-Blanchet et al, 1985;Gibas et al, 1986;Castedo et al, 1989a-c;Samaniego et al, 1990). T h e high incidence of additional numerical and other structural abnormalities of chromosome 12 underlines the important role of 12p and of genes located in this region, such as the KRAS protooncogene, in the development of G C T (Gibas et al, 1986;Samaniego et al, 1990;Rodriguez et al, 1992;Suijkerbuijk et al, 1991;Atkin et al, 1993). Moreover, the copy number of i( 12p) seems to be a prognostic marker (Bod et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Sections were counterstained with Mayer's hematoxylin which stains the nuclei blue in color germ cell marker, DAZL1, in the putative ontogenic progenitor, IGCN, and in the putative derivative, seminoma, provides further support for the hypothesis that IGCN is the precursor of germ cell neoplasia. Much effort has been expended in studying the origin and differentiation patterns of germ cell neoplasias using morphological, immunohistochemical; and genetic criteria [1,5,10,11,30]. Based on the model of a germ cell tumor's histogenesis [25], it is widely accepted that all forms of testicular germ cell tumors -with the notable exception of spermatocytic seminoma -are derived from a common precursor, originally recognized and described as IGCN and also designated as carcinoma in situ of the testis [23].…”
Section: Discussionmentioning
confidence: 99%